(untitled) (FAVE Sección Ciencias Veterinarias, 2021)
Learning evaluation of the topic “invariant components of scientific datum” in a Research methodology course. The learning of the topic invariant components of scientific datum was evaluated in the final exam of students who regularized the subject Methodology of research in the career of Veterinary Medicine of the National University of Rosario. A specially designed instrument was used, consisting of a text that includes the elements linked to each of the invariant components (entity, property, state and procedure), a work slogan and a table to complete by student’s responses. Of the 57 students evaluated, 38.6% responded correctly. 26.3% recognized the entity and 13.3% of them also recognized the property and its value, but not the procedure and 86.7% identified the procedure and the state, but not the property. In 35.1% of the students who did not identify correctly the entity, 35.0% identified the property and 65.0%, without recognizing either the entity or the property, correctly indicated the status and the procedure. These inconsistencies show the atomization of the reasoning process in face of the challenge of the problem to be addressed, and at the same time evince the existence of fragile knowledge.